A non-interventional cardiologist’s guide to coronary chronic total occlusions - Cilia, Lindsey; Megaly, Michael; Davies, Rhian; Tehrani, Behnam N.; Batchelor, Wayne B.; Truesdell, Alexander G. (Frontiers in Cardiovascular Medicine, 2024)
Coronary chronic total occlusions (CTO) are present in up to one-third of patients with coronary artery disease (CAD). It is thus essential for all clinical cardiologists to possess a basic awareness and understanding of CTOs, including optimal evaluation and management. While percutaneous coronary intervention (PCI) for CTO lesions has many similarities to non-CTO PCI, there are important considerations pertaining to pre-procedural evaluation, interventional techniques, procedural complications, and post-procedure management and follow-up unique to patients undergoing this highly specialized intervention.